The Effect of Gamma-rays on the Electrical Properties of Zr55Ni5Al10Cu30 Bulk Metallic Glass - L. H., Shah; Tsuchiya, B.; Nagata, S.; Shikama, T. (Elsevier, 2011)
We investigated the effects of gamma-ray irradiation on the electrical properties of Zr55Ni5Al10Cu30 bulk metallic glass (BMG) by monitoring the electrical resistivity–temperature dependence during heat treatment from room temperature to 823 K by using the four-point probe technique. X-ray diffraction (XRD) spectrum analysis was used to determine structural change after the process. It was found out that the electrical resistivity’s temperature dependency curve did not change due to increase of gamma ray dose. The XRD spectrum analysis confirmed the devitrification of samples after the annealing process and we observed the absence of body-centered-orthorhombic(bco)-Ni10Zr7 peaks in the irradiated samples’ spectrum after heat treatment.